A metaphysical character of war in the conceptions of E. Junger and J. Patocka - Sidorenko, Iryna (Actual Problems of Mind, 2017)
The paper presents a reconstruction of the «metaphysics of war» by involving the conception of a total mobilization by E.Junger and an existential-phenomenological philosophy by J. Patocka. The author claims that the modern «non-traditional» war embodies not the true unity of nations by Junger, or а solidarity experience by Patocka, but the policy of a militarized humanity, which leads to an escalation of violence.